The Starfish files : one leader's account of insight and inspiration under duress - Hiam, Alexander (HRD Press, 2005)
Have you ever wished you could only somehow get your people to tackle their work with a more positive attitude, a little more initiative, a shared feeling of ownership, and personal responsibility for their success? Here is a one-of-a-kind book that will inspire leaders like you to overcome problems and threats, break through to higher performance levels, and generate new enthusiasm in employees. A unique story about leadership that you will enjoy, learn from, and share with others. The Starfish Files uses an easily read story about some notes on business management and a leaders challenges to.